Influences on the knowledge and beliefs of ordinary people about developmental hierarchies - Binstock, Georgina (2013)
This article is motivated by the idea that development and developmental hierarchies have been constructed and embraced for centuries by scholars and policy makers and have been disseminated among ordinary people. Recent research shows that most people have constructions of development hierarchies that are similar across countries. In this article, we extend this research by examining how basic social factors influence ordinary people’s beliefs about development and developmental hierarchies in six countries: Argentina, China, Egypt, Iran, Nepal, and the United States. Results show that the understanding and perception of developmental hierarchies vary by gender and education. These results are important because they show how distinct groups of people have differential access to information or ideas.